Miskawayh (d. 1030) on Justice and The Limits of Law - Muchlisin, Annas Rolli (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
This article explores the limitations of Islamic law within the broader intellectual tradition of Islam. While law is typically designed to enforce coercive justice, Miskawayh’s perspective attempts to integrate this conception through a reassessment of the concept of justice. Specifically, this article examines, first, the overarching view of Islam as a nomothetic religion; and second, the ethical concepts and vision of justice offered by Miskawayh. By contextualizing Miskawayh’s ideas within the broader cultural and intellectual traditions of Islam, this research reveals a contrasting view of legal mechanisms. For Miskawayh, the vision of justice is not necessarily derived from external mechanisms of divine revelation, but rather hinges on the internal mechanisms of the individual. Miskawayh emphasizes a reversal of mechanisms from external to internal by advocating for a greater role of ethical-philosophical thought in Islamic legal discourse. Miskawayh, like many Muslim philosophers, navigates the relationship between revealed law and reason in his conception of justice. He rejects the notion of inherent conflict, arguing that both reason and divine law originate from God.